1991
DOI: 10.1104/pp.95.2.655
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Metabolism in the N-Limited Green Alga Selenastrum minutum

Abstract: We have determined the flow of "N into free amino acids of the N-limited green alga Selenastrum minutum (Naeg.) Collins after addition of 15NH4+ to aerobic or anaerobic cells. Under aerobic conditions, only a small proportion of the N assimilated was retained in the free amino acid pool. However, under anaerobic conditions almost all assimilated NH4, accumulates in alanine. This is a unique feature of anaerobic NH4+ assimilation. The pathway of carbon flow to alanine results in the production of ATP and reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 15 publications
3
14
0
4
Order By: Relevance
“…3). Vanlerberghe et al (1991) have argued that during the early stages of anaerobiosis, the amino group of aspartate is conserved by transaminating pyruvate to Ala. Similarly, we found that the decrease in aspartate over the first 8 h can account for the increase in Ala, since during this time a stoichiometry of approximately 1.08 mo1 of aspartate depleted per mo1 of Ala accumulated was observed.…”
Section: Ala and Aspartatesupporting
confidence: 51%
See 1 more Smart Citation
“…3). Vanlerberghe et al (1991) have argued that during the early stages of anaerobiosis, the amino group of aspartate is conserved by transaminating pyruvate to Ala. Similarly, we found that the decrease in aspartate over the first 8 h can account for the increase in Ala, since during this time a stoichiometry of approximately 1.08 mo1 of aspartate depleted per mo1 of Ala accumulated was observed.…”
Section: Ala and Aspartatesupporting
confidence: 51%
“…Because Ala synthesis requires N, it has been suggested that the N status of a tissue may be important in determining whether Ala is a significant fermentation end product (Hoffman et al, 1986;Good and Crosby, 1989b). Vanlerberghe et al (1991) have recently shown that under anaerobic conditions almost a11 of the assimilated N accumulates in Ala. Similarly, we found that in the absence of an N source and under anaerobic conditions, the Ala concentration did not reach the level found in plants grown in an N-rich medium, and decreases after 48 h. Presumably, the increase in Ala seen between 8 and 48 h is a result of the endogenous N supply, since our plants were not maintained in an N-limited environment prior to anaerobic induction.…”
Section: Fermentation Productsmentioning
confidence: 99%
“…Elevated levels of amino acids in the xylem sap (reported in more detail in this study) indicate extensive absorption and assimilation of NH 4 + in the roots. Furthermore, the production of alanine, the principal product of anaerobic N metabolism, is greatly enhanced in the presence of NH 4 + , a phenomenon reported previously by Vanleberghe and colleagues (Vanlerberghe and Turpin, 1990;Vanlerberghe et al, 1991). The question arises as to why this apparently efficient assimilation of NH 4 + does not lead to dry matter accumulation under hypoxia above that seen with the N-free treatment.…”
Section: Discussionmentioning
confidence: 65%
“…The hypothesis that aspartate is a precursor of alanine synthesis is also supported by the fact that when symbiotic plants are flooded and aerated (aerated hydroponics), where alanine is not formed because the roots do not become hypoxic, aspartate levels in the xylem increase to high levels and do not fall (Lima and Sodek, 2003). Vanlerberghe et al (1991) also concluded that aspartate was the precursor of alanine during anaerobiosis of Selenastrum in the absence of an external N source.…”
Section: Discussionmentioning
confidence: 72%
“…Plants in which hexokinase has been manipulated showed altered response to anaerobic stress and change in transcription of the anaerobic response proteins. Nitrogen metabolism and exogenous nitrate supply might also be important in anoxia tolerance (Van Lerberghe et al, 1991 ;Fan et al, 1997 ;Vartapetian & Polyakova, 1999). Intolerant plants show NADH accumulation within a few minutes of the stress (Roberts et al, 1984).…”
Section: Anaerobic Stress and Flooding Tolerance Of Plantsmentioning
confidence: 99%